Impacts of Post-metallisation Processes on the Electrical and Photovoltaic Properties of Si Quantum Dot Solar Cells - Di, Dawei (Springer, 2010)
As an important step towards the realisation of silicon-based tandem solar cells using silicon quantum dots embedded in a silicon dioxide (SiO(2)) matrix, single-junction silicon quantum dot (Si QD) solar cells on quartz substrates have been fabricated. The total thickness of the solar cell material is 420 nm. The cells contain 4 nm diameter Si quantum dots. The impacts of post-metallisation treatments such as phosphoric acid (H(3)PO(4)) etching, nitrogen (N(2)) gas anneal and forming gas (Ar: H(2)) anneal on the cells’ electrical and photovoltaic properties are investigated. The Si QD solar cells studied in this work have achieved an open circuit voltage of 410 mV after various processes. Parameters extracted from dark I–V, light I–V and circular transfer length measurement (CTLM) suggest limiting mechanism in the Si QD solar cell operation and possible approaches for further improvement.